How South Korean female university students perceive women’s beauty standards and their connotations - Ludwiczak, Izabela (My University, 2021)
Thesis is focused on the topic of South Korean women’s beauty standards from the perspective of the female university students. Topic besides beauty standards focuses on their connotations – K-beauty and plastic surgeries. Goal of the paper is to investigate how beauty influences social life of Koreans. Thesis is based on the 4 semi-structured interviews I conducted and previous studies. Beauty standards in Korea are defined by media, current ideals for perfect beauty are white skin, small face, big eyes and skinny body. Due to constant exposure of beautiful people by media women feel pressure to look attractive. Make-up and plastic surgeries are to methods which usually women use to change their looks. Make-up is the easiest way but seems to not be that popular among students. Plastic surgery is something more invasive. Double eyelid surgery is the most popular type of plastic surgery among Koreans. When it comes to the influence of beauty on the social life appearance is valuable. Good look seems to have insignificant impact on creating relationships. The same can be said about work life as looks mostly are meaningful at the job interview. Marriage prospects may be influenced by appearance, but it mostly depends on a person. Different areas are affected by good appearance to a different degree.
Keywords: beauty standards, South Korea, K-beauty, plastic surgery